2015
DOI: 10.1126/sciadv.1500686
|View full text |Cite
|
Sign up to set email alerts
|

Accretion-induced variability links young stellar objects, white dwarfs, and black holes

Abstract: Astrophysical accretion is a universal process in objects from proto-stars to supermassive black holes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 51 publications
11
85
0
Order By: Relevance
“…These features, claimed as universal characteristics of accretion-powered sources (e.g. Scaringi et al 2015Scaringi et al , 2012, have also been observed in the emission of the most under-luminous SMBH Sgr A * located at the center of our galaxy (Meyer et al 2014;Witzel et al 2012;Dodds-Eden et al 2011;Meyer et al 2009). These phenomenological similarities across a wide range of mass scales (∼ 10 orders) have further led to the claim that the physics of accretion is universal, irrespective of accretor physical details.…”
Section: Introductionsupporting
confidence: 68%
“…These features, claimed as universal characteristics of accretion-powered sources (e.g. Scaringi et al 2015Scaringi et al , 2012, have also been observed in the emission of the most under-luminous SMBH Sgr A * located at the center of our galaxy (Meyer et al 2014;Witzel et al 2012;Dodds-Eden et al 2011;Meyer et al 2009). These phenomenological similarities across a wide range of mass scales (∼ 10 orders) have further led to the claim that the physics of accretion is universal, irrespective of accretor physical details.…”
Section: Introductionsupporting
confidence: 68%
“…Linear rms-flux relations are also present in the X-ray variability from ultraluminous X-ray sources (Heil & Vaughan 2010;Hernández-García et al 2015) as well as the short-time-scale optical variability of a blazar (Edelson et al 2013). Expanding its scope beyond the most compact accreting objects, linear rms-flux relations are found in the broadband noise variability seen from accreting white dwarfs (Scaringi et al 2012; Van de Sande et al 2015;Dobrotka & Ness 2015) and even in young stellar objects (YSOs, Scaringi et al 2015).…”
Section: Introductionmentioning
confidence: 85%
“…In fact, the phenomenology we seek to understand is also readily observed in CV systems (Scaringi et al 2012a(Scaringi et al , 2012b(Scaringi et al , 2014 and young stellar objects (YSOs, Scaringi et al 2015). These systems are non-relativistic and not hot enough to be largely affected by radiation pressure in the disk.…”
Section: Discussionmentioning
confidence: 99%